Interactive Multimedia Based Mathematics Problem Solving to Develop Students’ Reasoning - Faizal Amir, Mohammad; Nur Hasanah, Fitria; Musthofa, Hamsyah (International Journal of Engineering and Technology, 2018)
The progress of information and communication technology demands lecturer of mathematics to make innovative learning based on IT while focusing the main goal in learning mathematics, i.e to create students who are skilled in solving problems and have good mathematical reasoning. Therefore, an interactive mathematical development based on problem solving is required. The model is developed using ADDIE (Analysis, Design, Development, Implementation, Evaluation). The data is analyzed using both Quantitative (as the main data) and qualitative (as supporting data). The results showed that interactive mathematical multimedia significantly improved the students’ mathematical reasoning in terms of analyzing data, proposing allegations, verifying, drawing conclusions, and examining the validity of arguments. Students’ responsiveness and motivation to learn mathematics is also positive because multimedia has interactive video display and complete material, while students feel that the learning process is not limited by space and time. Â Â